La importancia del capital humano en la organización (2019)
The purpose of this paper is to highlight the importance of the global concept of human capital in the organization framed in a current context, where it is crucial to analyze the internal and external factors that play a key role in the development of each society .This implies the detail in the lack of exploitation of the potential and resources that were previously not used by the industries and the lack of evidence of an organizational commitment capable of carrying out competition in the form of innovation.